2015
DOI: 10.1103/physrevb.91.035423
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of Dirac fermions in a buckled honeycomb lattice

Abstract: We calculate the magnetic response of a buckled honeycomb lattice with intrinsic spin-orbit coupling (such as silicene) which supports valley-spin polarized energy bands when subjected to a perpendicular electric field Ez. By changing the magnitude of the external electric field, the size of the two band gaps involved can be tuned, and a transition from a topological insulator (TI) to a trivial band insulator (BI) is induced as one of the gaps becomes zero, and the system enters a valley-spin polarized metalli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 60 publications
(169 reference statements)
5
34
0
Order By: Relevance
“…Band-gap engineering may mitigate this problem: band gap may be switched on and off by strain [44]; alternatively, an external electric field applied in a direction perpendicular to the buckled lattice can induce charge imbalance between the sublattices, and open a band gap [44]. In addition, a variable perpendicular electric field can induce a phase transition from a topological insulator to a trivial band insulator, passing through a valley-spin polarized metal [45], and can also induce superconducting states when doped. A tunable quantum phase transition from a singlet chiral d + id'-wave pairing phase to a triplet f-wave phase could occur, provoking an increase in the superconducting critical temperature [46].…”
Section: Spin-orbit Coupling (Soc) Can Open a Band Gap At The Otherwimentioning
confidence: 99%
“…Band-gap engineering may mitigate this problem: band gap may be switched on and off by strain [44]; alternatively, an external electric field applied in a direction perpendicular to the buckled lattice can induce charge imbalance between the sublattices, and open a band gap [44]. In addition, a variable perpendicular electric field can induce a phase transition from a topological insulator to a trivial band insulator, passing through a valley-spin polarized metal [45], and can also induce superconducting states when doped. A tunable quantum phase transition from a singlet chiral d + id'-wave pairing phase to a triplet f-wave phase could occur, provoking an increase in the superconducting critical temperature [46].…”
Section: Spin-orbit Coupling (Soc) Can Open a Band Gap At The Otherwimentioning
confidence: 99%
“…Moreover, graphene and the α-T 3 lattice both exhibit particlehole symmetry breaking under the influence of both modulations. Very recently, the Carbotte group has shown that a small asymmetry in the energy band can be very sensitive to magneto-optical excitation 56,57 . Therefore, we conclude that the combination of both modulations can be used as a tool to break the particle-hole symmetry for manipulation of the valley degree of freedom in optical devices.…”
Section: Discussionmentioning
confidence: 99%
“…The results of Fig. 3(a), dashed curve, can be reduced to those of single-valley gapped graphene for ∆ h = 0 [26], irrespective of a factor of 2 due to valley degeneracy, and to those of gapped TIs [31]. However, for ∆ Ω > ∆ h = 0 only one surface must be considered, see Fig.…”
mentioning
confidence: 92%